2019
DOI: 10.1111/bjhp.12355
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional relationship of stress and affect with physical activity and healthy eating

Abstract: Objectives Physical activity and healthy eating seem to be protective against experiencing stress and negative affect as well as increase positive affect. At the same time, previous studies showed that people reduce salutogenic behaviours such as physical activity and healthy eating in the face of stress and negative affect while increasing such behaviours in the context of positive affect. Due to daily fluctuations of these behaviours, the present study examined these relationships in daily life using ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
153
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(182 citation statements)
references
References 91 publications
18
153
0
11
Order By: Relevance
“…However, there is now more evidence emerging from cohort and intervention studies, and the overall evidence supports that a link exists [50,51]. In terms of the direction of the relationship between diet and mental health, this is a complex and likely bi-directional relationship [52]. There are indications for a healthy diet contributing to improved mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is now more evidence emerging from cohort and intervention studies, and the overall evidence supports that a link exists [50,51]. In terms of the direction of the relationship between diet and mental health, this is a complex and likely bi-directional relationship [52]. There are indications for a healthy diet contributing to improved mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there are indications that dietary choices are influenced by mental health status. For example, studies have shown that individuals often make less healthy dietary choices during periods of stress or to alleviate feelings of stress [52]. The relationship between diet and mental health is complex with many more factors at play and requires further investigation among a range of population groups, including university students.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas trait emotional eating status did not explain unhealthy snacking, self-reported habitual snacking and dietary restraint did explain unhealthy snacking. Various other studies showed that negative affect did not relate to subsequent unhealthy eating (70) , snack intake (25) or subclinical pathological eating behaviour such as eating large amounts of food (71) , or even related to decreased subsequent energy consumption (72) in healthy individuals.…”
Section: Evidence From Naturalistic Researchmentioning
confidence: 99%
“…On the whole, the results of the relatively few animal and human studies suggest that the use of probiotics might be beneficial to mood, particularly in individuals with a history of mood disorders. In a different direction, there are also studies showing a correlation between physical activity and stress levels, with physical activity generally promoting beneficial effects on mood and affective state [180,181]. From a biochemical perspective, a positive correlation between physical exercise and the levels of tryptophan was described by Gostner et al [182]: The authors suggested that physical exercise allows for increased levels of tryptophan which-once taken-up by the brain-may boost the synthesis of serotonin, subsequently leading to an increase in mood state.…”
Section: Probioticsmentioning
confidence: 99%